Designing Trials with Purpose: Pragmatic Clinical Trials of Nonpharmacological Approaches for Pain Management. (10th December 2020) - Gordon, Kirsha S; Peduzzi, Peter; Kerns, Robert D
Abstract: Objective: Pain is one of the most significant causes of morbidity and disability worldwide. The efficacy of several nonpharmacological approaches for pain management has been established, but significant gaps exist between this evidence and their limited availability and use in routine clinical practice. Questions remain about their effectiveness and how best to integrate them in usual care to optimize patient-centered outcomes. Pragmatic clinical trials (PCTs) may help address this gap. Informed by the Pragmatic Explanatory Continuum Indicator Summary (PRECIS-2), we sought to describe the key features of optimized PCTs of nonpharmacological approaches for the management of pain and common co-occurring conditions. Methods: To accomplish this objective, we searched the published literature on PCTs of nonpharmacological pain management approaches from 2010–2019 and applied the PRECIS-2 criteria. We discuss key PRECIS-2 domains of interest for designing and performing PCTs and cite specific examples from the published literature as potential models for future PCTs. Results: We found 13 nonpharmacological PCTs. They were heterogeneous in size, recruitment, follow-up time, and location. The lessons learned from these studies led us to explicate key features of trials on the explanatory–pragmatic continuum across the PRECIS-2 domains that can be used by future investigators when designing their clinical trials of nonpharmacological approaches to pain management. Conclusions: We encourage the increased application of PCTs to produce timely and valuable results and products that will inform the development of safe and effective integrated pain care plans that optimize important patient-centered outcomes.